What Motivates Malaysians To Engage In Social Commerce Shopping? - Wan Rasyidah Wan Nawang; Raja Azhan Raja Mamat; Intan Fatimah Anwar (Universiti Malaysia Sabah, 2025)
Social media have wrought significant change since their inception. They have grown by leaps and bounds, transitioning from social networks to a powerful shopping platform known as social commerce. While some users embrace this technology, others opt out for various reasons. The objective of this study is to examine the factors that influence Malaysian consumers' social commerce shopping intentions. The extended technology acceptance model (TAM) was used to develop the conceptual framework. An online questionnaire was distributed across several social media platforms. Using convenience sampling, a total of 233 Malaysians participated in the study. The data was analyzed using multiple regression analysis. The study found that perceived enjoyment, trust, and electronic word of mouth (eWOM) had a significant influence on Malaysian consumers' social commerce purchase intentions, while perceived usefulness, perceived ease of use, and social influence did not. Trust is the most influential factor affecting Malaysian consumers' purchase intentions in social commerce, followed by perceived enjoyment and eWOM. This study hopes to add to the limited knowledge on social commerce and consumer behavior and provide retailers and marketers of social commerce with insights that will enable them to better understand their customers' preferences and, in turn, provide better service.